Persistent Bacterial Vaginosis and Risk for Spontaneous Preterm Birth - Blumenfeld, Yair J.; Marić, Ivana; Stevenson, David K.; Gibbs, Ronald S.; Shaw, Gary M. (American Journal of Perinatology, 2023)
Objective The aim of this study was to determine the association between persistent bacterial vaginosis (BV) in pregnancy and risk for spontaneous preterm birth (sPTB).Study Design Retrospective data from IBM MarketScan Commercial Database were analyzed. Women aged between 12 and 55 years with singleton gestations were included and linked to an outpatient medications database and medications prescribed during the pregnancy were analyzed. BV in pregnancy was determined based on both a diagnosis of BV and treatment with metronidazole and/or clindamycin, and persistent treatment of BV was defined as BV in more than one trimester or BV requiring more than one antibiotic prescription. Odds ratios were calculated comparing sPTB frequencies in those with BV, or persistent BV, to women without BV in pregnancy. Survival analysis using Kaplan–Meier curves for the gestational age at delivery was also performed.Results Among a cohort of 2,538,606 women, 216,611 had an associated International Classification of Diseases, 9th Revision or 10th Revision code for diagnosis of BV alone, and 63,817 had both a diagnosis of BV and were treated with metronidazole and/or clindamycin. Overall, the frequency of sPTB among women treated with BV was 7.5% compared with 5.7% for women without BV who did not receive antibiotics. Relative to those without BV in pregnancy, odds ratios for sPTB were highest in those treated for BV in both the first and second trimester (1.66 [95% confidence interval [CI]: 1.52, 1.81]) or those with three or more prescriptions in pregnancy (1.48 [95% CI: 1.35, 1.63].Conclusion Persistent BV may have a higher risk for sPTB than a single episode of BV in pregnancy.Key Points
Keywords: bacterial vaginosis; spontaneous preterm birth; persistent